An intervention programme to improve spiritual intelligence among Iranian adolescents in Malaysia - Hosseini, Maryam; Elias, Habibah; Krauss, Steven Eric; Hassan, Siti Aishah (Universiti Putra Malaysia Press, 2012)
The aim of this study was to determine whether an intervention program on Spiritual Intelligence will help to improve spiritual intelligence among Iranian female adolescents studying in an Iranian School in Kuala Lumpur, Malaysia. The sample comprised of 32 female students, 16 assigned to the experimental group and another 16 in the control group. The study utilized the quasi experimental design with a pre-test and a post-test. The experimental group was given 5 sessions of training in spiritual intelligence (SIG Training) over a period of 5 weeks. The control group was given life skills training for the duration of the experiment. Spiritual intelligence was measured by Integrated Spiritual Intelligence Scale (ISIS) by Amran and Dryer (2007). Results showed that the SIG training improved spiritual intelligence in the experimental group as well as the subscales in spiritual intelligence. The subscale ‘Gratitude’ showed a significant increase when a comparison was made between the pre-test and post-test in the experimental group. The control group showed a significant increase in one subscale namely ‘purpose’ but there was no significant change for the other subscales. Hence, the training given to the experimental group was effective in enhancing spiritual intelligence.